The efficacy of modified Viennese manual perineal protection (VMPP) versus conventional technique in perineal protection at second stage of labour: A randomize case control study - Jenal, Ruztini; Nusee, Zalina; M. Aris, Zulpadli; Ismail, Hamizah; Pasi, Hafizah (2016)
Introduction: The modified Viennese manual perineal protection (VMPP) is a modified method based on an experimental study on a computerized biomechanical model of the perineum by Jansova and colleagues. It determines the exact placement of fingers on the perineum that has less perineal tension with the minimal perineal injury. Aim: To evaluate the effectiveness of modified VMPP in protecting the perineal injury and need of episiotomy compared to conventional method. The associated risk factors for perineal injury were also identified. Methodology: A randomize case control study on laboring women without previous vaginal delivery at the tertiary hospital. The modified VMPP was based on a method described by Jansova et al., (2014). The sanitary pad was used to support and protect perineum in the control group. Result: A total of 158 women were recruited and divided into modified VMPP group (n=71) and control group (n=78). Nine cases were excluded due to instrumental deliveries. Thirty two (21.5%) women had intact perineum mainly in modified VMPP group (p=0.022).There were 81 (54.4%) cases of first degree perineal tear, 16 (10.7%) second degree tear and 26 (18.7%) required episiotomy which is more in the control group (p=0.548). None of the participants suffered third or fourth degree perineal tears. The more advanced maternal age, the higher BMI and larger infant’s head circumference, the higher risk of perineal injury. Conclusion: Modified VMPP is effective in minimizing perineal injury and less need for an episiotomy. The risk of perineal injury is higher with increasing maternal age, BMI and fetal head circumference.